Hubungan Frekuensi Konsumsi Lemak, Tingkat Pemenuhan Asupan Lemak, dan Kualitas Tidur dengan Kejadian Gastritis pada Mahasiswi Gizi Angkatan 2023-2024 UNESA - Evelyna Clarissa Adristi; Choirul Anna Nur Afifah (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Gastritis incidence is relatively high in East Java, reaching 44.5%. Gastritis, condition characterized by chronic or acute inflammation of stomach lining, and common among productive age, including female students. Gastritis influenced by dietary habits and daily sleep quality. This study to determine the relationship between frequency fat consumption, level fat intake fulfillment, and sleep quality with gastritis incidence in Female Nutrition Students of 2023-2024 Class UNESA. This study used a quantitative cross-sectional design, and data collected using purposive sampling. Respondent’s study were 92 Female Nutrition Students from 2023-2024 Class UNESA. Frequency fat consumption and level fat intake fulfillment collected by Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) interviews, sleep quality collected by Pittsburgh Sleep Quality Index (PSQI) questionnaire, and gastritis incidence collected from medical history based on a doctor’s diagnosis. The data were analyzed using Chi-Square test. The results showed that there was no relationship between frequency fat consumption (p-value=0.254) and level fat intake fulfillment (p-value=0.295) with incidence of gastritis, however, there was a relationship between sleep quality (p-value=0.010) and incidence of gastritis in Female Nutrition Students of 2023–2024 Class UNESA. Therefore, Female Nutrition Students of 2023-2024 Class UNESA are advised to improve sleep quality to reduce their risk of gastritis.